MORAL EDUCATION VALUES IN IMAM AL-GHAZALI'S MINHAJUL MUTA'ALLIM: Its Relevance for Contemporary Islamic Character Education - Muhamad Rifqi Maulana; Ahmed Shoim El Amin (MUJADDID: Journal Islamic Study and Philosophy, 2026)
The moral crisis among students in the contemporary era has become a significant challenge for educational institutions worldwide. Islamic education emphasizes moral development as an essential component of human perfection, and Imam Al-Ghazali remains one of the most influential scholars in this field. This study aims to analyze the moral education values contained in Minhajul Muta'allim and examine their relevance to contemporary Islamic character education. This research employs a qualitative library research approach using content analysis. Primary data were obtained from Imam Al-Ghazali's Minhajul Muta'allim, while secondary data were collected from books, scholarly journals, and related studies on Islamic moral education. The findings reveal that Al-Ghazali's moral education framework emphasizes sincerity in seeking knowledge, respect for teachers, self-discipline, humility, patience, spiritual purification, and social responsibility. The study further demonstrates that moral formation is achieved through habituation, self-control, and continuous ethical training. These values remain highly relevant in addressing modern educational challenges, including moral degradation, individualism, and the excessive orientation toward material success. The study concludes that Al-Ghazali's educational philosophy provides a holistic framework that integrates intellectual development, spiritual awareness, and ethical responsibility, making it applicable to contemporary Islamic educational institutions.